From the little chapters to the big questions : how were the Croatian glagolitic breviaries and missals compiled? - Šimić, Ana, lingvistkinja (Array, 2020)
This paper deals with textual transmission in pre-Tridentine Croatian Glagolitic missals and breviaries. Previous research has demonstrated that northern (Krk-Istria) codices follow earlier translations from Greek, whereas southern (Zadar-Krbava) codices have been adjusted to Latin exemplars. However, this differentiation is not clear-cut – certain codices are recognised as a combination of the northern and southern group. The paper addresses the inability to establish a stemma codicum, explaining this through both the high loss rate of Croatian Glagolitic codices and horizontal textual transmission (the usage of more than one exemplar). Further insight into the given topic is provided through discussion of the types of Glagolitic scribes (simple scribe, scholar-scribe, redactor-like scribe, and redactor-scribe) and the determinants of their work, the most prominent of which is the absence of authorial authority. The core of the paper is the study of little chapters as texts shared between breviaries and missals. Data analysis suggests the two liturgical books share a common origin, and that each was likely used as a source for the other. Moreover, data analysis also broadens the notion of the polygenetic origin of Croatian Glagolitic books, which should be understood not only in terms of successive contaminations, but simultaneous contaminations as well. Both types of contamination are sometimes extra-stemmatic, which means that different kinds of sources were used by Glagolitic scribes during copying (including older Glagolitic missals and breviaries, other Church Slavonic books such as the Prophetologion or Apostolos, and personal memory). The paper offers an explanation as to why it is unlikely that a Glagolitic Bible and Latin exemplars were (commonly) used as sources.